THE PROBLEM OF EMOTIONAL STABILITY AND STRESS RESISTANCE IN EDUCATIONAL PROCESSES (Eureka Journal of Education & Learning Technologies, 2026)
This article presents an analysis of scholars’ views on the nature and causes of stress and misunderstandings encountered in contemporary educational processes.
Keywords: Stress, distress, physiological stress, psychological stress, mechanism, adaptation, nervous tension, emotional arousal, stimulus, stressor.